2018
DOI: 10.1021/acs.macromol.7b01519
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chain Flexibility and Interlayer Interactions on the Local Dynamics of Layered Polymer Systems

Abstract: Layered polymeric systems are widely used in membrane separation applications; chain mobility in these layered systems is a key consideration in the design of the membranes. The transport properties of membrane polymers can be significantly altered by the perturbations in chain dynamics induced by the presence of an interface and also by the topological properties of the polymers constituting the layered systems. In this work, we use molecular dynamics (MD) simulations to determine the effects of polymer backb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 73 publications
(96 reference statements)
1
18
0
Order By: Relevance
“…A localized fluorescence method is used to measure the local T g ( z ) of a thin pyrene-labeled PS probe layer placed at a distance z from the PS/PDMS interface. These findings demonstrate that the breadth of the compositional interface between the two dissimilar polymers and the modulus of the neighboring domain are key factors controlling the T g ( z ) behavior, providing insight for related theoretical efforts in the field ,,,, into the control parameters responsible for this phenomenon. Characterization of the local properties near the interface of PS/PDMS, in particular, are relevant for a range of applications from mechanical reinforcement of polymers , to the buckling-based metrology used to measure the modulus of ultrathin glassy films. …”
mentioning
confidence: 70%
See 1 more Smart Citation
“…A localized fluorescence method is used to measure the local T g ( z ) of a thin pyrene-labeled PS probe layer placed at a distance z from the PS/PDMS interface. These findings demonstrate that the breadth of the compositional interface between the two dissimilar polymers and the modulus of the neighboring domain are key factors controlling the T g ( z ) behavior, providing insight for related theoretical efforts in the field ,,,, into the control parameters responsible for this phenomenon. Characterization of the local properties near the interface of PS/PDMS, in particular, are relevant for a range of applications from mechanical reinforcement of polymers , to the buckling-based metrology used to measure the modulus of ultrathin glassy films. …”
mentioning
confidence: 70%
“…High-performance multicomponent materials have nanostructured morphologies where the desired global properties are obtained from an amalgam of local property changes caused by the multitude of internal interfaces. Studies on thin polymer films have demonstrated a host of property changes with decreasing film thickness attributed to interface effects, including polymer–polymer interfaces. The efficient design of multicomponent materials requires the understanding of how these interface effects perturb local properties. Glassy–rubbery interfaces between polymer domains impart material toughness and flexibility , and can be used to tune phononic transport .…”
mentioning
confidence: 99%
“…In this research, by adding PEG, the field for modifying the gas separation properties of the polysulfone membrane has been provided. The type of chains' development has an important role in diffusion properties from membrane due to morphology, crystallization, compression and glass transition temperature of membrane [13][14][15]. Finding structure and properties of polymeric membranes are key factors to obtain better efficiency of gas separation from membrane.…”
Section: Introductionmentioning
confidence: 99%
“…11,[15][16][17][18][19]22 Lang et al also perfomed molecular dynamics (MD) simulation study regarding the effects of polymer−polymer interaction energy and hardness of confining polymer on change in T g of confined polymers. i v i d u a l n o t d i r e c t l y a s s o c i a t e d w i t h s c i t e i s p r o h i b i t e d .…”
mentioning
confidence: 99%
“…In addition to polymer–solid and polymer–air interfaces, studies have recently focused on polymer structure and properties, such as T g and dynamics of nanoconfined polymers, near polymer–polymer interfaces. The contribution of the region near the polymer–polymer interface in polymer blend systems is not ignorable if the domain size is sub-100 nm, and the interface predominantly influences the overall blend structure and properties. , In this respect, understanding the local dynamics is clearly necessary. We have previously investigated the diffusion dynamics of PMMA/ d PMMA confined between graphene oxide (GO) sheets (GO/PMMA/ d PMMA/GO) using the neutron reflectivity (NR) technique .…”
mentioning
confidence: 99%